Some enzymatic activities registered in eggs and gut tissues of the olive fruit fly, Dacus oleae (Gmelin) - Stamopoulos, D. C. (ENTOMOLOGIA HELLENICA, 1988)
Nineteen enzymatic activities of eggs, gut tissues of larvae and adults of Dacus oleae have been determined using the API-ZYM micromethod. The enzymatic activities of eggs were much weaker than those of larval or adult guts. The activities increased progressively to the L2 and L3. The lack of feeding caused a reduction of certain activities in larvae (alkaline phosphatase, esterases, aminopeptidases) but not in adults. The addition of streptomycin to the food of adults, to obtain “aposymbiotic” individuals, did not have a clear effect on the activities of the insect’s various stages. Although the enzymes studied were not the only ones that occur in the insect’s gut tissues, it seems that there are few similarities between the enzymatic system of larvae and that of adults, most probably because of the different content of the two diets in essential nutrients such as amino acids, proteins, and lipids.